Eco-Efficient Analysis of a Refurbishment Proposal for a Social Housing - Mercader-Moyano, Pilar; Esquivias, Paula M.; Muntean, Radu (MDPI AG, 2020)
In recent years, the building sector has been turning towards intervening in the existing city building stock. In fact, it is generally accepted that the refurbishment of buildings based on sustainability must form the axis of reformulation of the building sector. Although energy refurbishment is commonly accepted and recommended towards decarbonization of the building stock, an integral assessment towards implementing the principles of the circular economy must incorporate the environmental impact of the materials in order to get an eco-efficient refurbishment. The article presents the environmental analysis of a social housing located in Cadiz (Spain) and the improvements achieved by its refurbishment. This intervention is improved by incorporating eco-efficient materials based on the environmental and life cycle analysis (LCA). Those analyses are performed using EnergyPlus, Radiance, LCA standards, and Environmental Product Declaration of the products. The results shown that although an energy rehabilitation intervention can fulfil other eco-efficient aspects, an integral assessment should always be carried out in order to ensure that indoor comfort is achieved, daylighting and solar heat gains are balanced, and the environmental impact at product, use, and end-of-life stages of a building is minimized. Considering the constrains and limitations of the tools and databases, higher efforts should be done to solve them and provide useful resources for a decarbonized and circular building stock.